152 Effects of a solar-powered cooling system on performance of heat-stressed lactating sows. (30th November 2020) - Johnston, Lee; Reese, Mike; Buchanan, Eric; Li, Yuzhi; Hilbrands, Adrienne; Lozinski, Brigit; Tallaksen, Joel; Janni, Kevin; Hetchler, Brian; Cortus, Erin
Abstract: We hypothesized that a solar-powered system designed to cool heat-stressed sows would improve sow performance and reduce use of fossil fuels in farrowing rooms. To test this hypothesis, we used two mirror-image, farrowing rooms equipped with 16 farrowing stalls each. Each farrowing stall in the COOLED room was equipped with a cooled flooring insert (Nooyen Manufacturing) under the sow and a single nipple drinker delivering chilled drinking water. Circulating water cooled by a water-source heat pump that was powered by a 20 kW photovoltaic solar array cooled the floor inserts (15 to 18°C) and chilled the drinking water (13 to 15°C). Heat harvested from sows partially warmed water (43 to 48°C) that circulated through pads in the piglet creep area. The CONTROL room was nearly identical to the COOLED room except there was no cooling and supplemental heat for piglets was provided by one heat lamp (125 W) per farrowing stall or an electric heating pad (Innovative Heating Technologies). Three farrowing groups were studied during summer and room heaters kept rooms above 24°C to ensure sows were heat stressed. Electric consumption in COOLED and CONTROL rooms was measured. Data were analyzed using Proc Glimmix with room treatment as a fixed effect and farrowing group as a random effect. The cooling system reduced sow respiration rate and body temperature (Table 1) which increased feed intake and reduced weight loss of sows over the 21-day lactation. However, the cooling system did not increase litter size or weight at weaning. Electricity use in the CONTROL room (26.4 kWh/d) was lower (P< 0.01) than the COOLED room (79.6 kWh/d). The solar array produced 91 kWh/d on average. In conclusion, the cooling system studied partially mitigated heat stress of lactating sows but did not improve sow performance and did not noticeably reduce consumption of fossil fuels.